The value of school: Educational experiences and maturational growth among delinquent youth - Abeling-Judge, David (Journal of developmental and life-course criminology, 2021)
Maturational growth through psychosocial, adult role, identity, civic, and cognitive change has proven an insightful explanation of behavioral change among offender populations. It has evolved to address both endogenous growth, such as advancing age, and exogenous influences, such as family. The relevance of family bonding processes to maturation is well documented, in both psychological and criminological work, but an unexplored social process of relevance may be education. The current study uses the longitudinal Pathways to Desistance Study to explore the influence of school orientation variables and teacher bonding connections on specific domains of maturational growth as articulated by the integrated maturation theory. Analyses address the distinct influences of schools attended in the general community and schools attended while under placement in a secure juvenile detention facility. The current study identifies significant within-individual variation in various domains of maturity influenced by community school bonds, with corresponding patterns emerging for institutional school bonding experiences. Relationships with teachers produce some positive change, but the results are not consistent. Educational processes play a significant role in facilitating maturational growth, independent of family influences. This pattern emerges across different contexts, expands theoretical insight, and suggests focused policy interventions to promote desistance.